Garfield slurps and burps - Davis, Jim, 1945 July 28- (New York : Ballantine Books, 2019)
Who has time for manners when there's food to be inhaled? Garfield eschews etiquette in favor of bingeing and belching. And who can blame him? He's only human! So get rude 'n' crude and pig out on this all-new collection of tasty comics. SLURP! SLURP! SLURP!
3.4
5-8
Keywords: Garfield -- (Fictitious character) -- Comic books, strips, etc. -- Fiction; Cats -- Comic books, strips, etc. -- Fiction; Human-animal relationships -- Comic books, strips, etc. -- Fiction; Humorous stories; Garfield -- (Fictitious character) -- Juvenile fiction; Cats -- Juvenile fiction; Human-animal relationships -- Juvenile fiction; Humorous stories; Cartoons and comics; Humorous comics; Comics (Graphic works); Graphic novels